Wuity as a Philosophical Lens for Qualitative Data Analysis. (18th June 2020) - Williamson, Charmaine; Van Rooyen, Annelien; Shuttleworth, Christina; Binnekade, Carol; Scott, Deon
Qualitative researchers place value on taking a closer, insider look at data as well as the subsequent data analysis and interpretation. On one end of the interpretive spectrum, researchers should be fully imbued with the coding-to-theorizing process by attending closely to the coding that leads to their analysis. On the opposite end, are those researchers positioned in the positivist paradigm, who vividly question the "researcher-as-data" analysis and its explicit subjectivity. As a middle ground, qualitative researchers have worked collectively in broader teams and/or used independent, practiced coders to add rigor to the coding process. These approaches clearly reflect the philosophical positions researchers adopt in following a research process. For the current study, the authors used the framework of Wuity thinking, which prompts exploratory learning and draws on Eastern-based wisdom. By using Wuity as both a method and a theory, an independent coder with prior knowledge of the coding process oriented a team into the epistemic practices of qualitative coding. The study found that the subtleties of a Wuity lens show delicate and enabling thresholds for expanding mindsets and practices within epistemic communities. The authors concluded that a coding team, working in a different manner, may well advance novel points of departure for qualitative analysis.